Sediment Resuspension and Associated Extracellular Enzyme Activities Measured ex situ: A Mechanism for Benthic-Pelagic Coupling in the Deep Gulf of Mexico - Kai Ziervogel (Frontiers Media S.A., 2021)
Sediment resuspension caused by near-bed currents mediates exchange processes between the seafloor and the overlying water column, known as benthic-pelagic coupling. To investigate the effects of sediment resuspension on microbial enzyme activities in bottom waters (<500 m), we conducted onboard erosion experiments using sediment cores taken with a multi-corer from six deep-sea sites in the northern Gulf of Mexico. We then incubated the core-top water with resuspended sediments in roller tanks to simulate bottom water conditions following sediment resuspension. Bacterial cell abundance, particulate organic matter content, and potential rates of three hydrolytic enzymes (leucine aminopeptidases – PEP; β-glucosidases – GLU, lipases – LIP) were monitored during the experimentally-generated erosion events and subsequently in the roller tanks to examine whether resuspension of deep-sea sediments enhances activities of extracellular enzymes in overlying waters. Surficial sediments were resuspended at critical shear stress velocities between 1.4 and 1.7 cm s–1, which parallel bottom water currents of 28 and 34 cm s–1. Only one of our nine cores resisted experimentally generated bottom shear stresses and remained undisturbed, possibly as a result of oil residues from natural hydrocarbon seeps at the investigated site. The most notable enzymatic responses to sediment resuspension were found for LIP activities that increased in overlying waters of all eight of our resuspended cores and remained at high levels during the roller tank incubations. PEP and GLU showed orders of magnitude lower rates and more variable responses to experimentally resuspended sediments compared with LIP. We also found a disconnect between enzyme activities and bacterial cell numbers, indicating a major role of extracellular enzymes physically disconnected from microbial cells in our experiments. Our results demonstrate that sediment resuspension may promote organic matter breakdown in bottom waters by supplying extracellular enzymes without requiring a bacterial growth response. The marked increase in LIP activity suggests that resuspended enzymes may affect the degradation of petroleum hydrocarbons, including those from the natural seeps that are abundant in the investigation area.